Sosoialisasi Pencegahan Bullying pada Murid SDN 18,26,22,41,38 Sungai Limau, Untuk Meningkatkan Partisipasi dan Antusiasme Siswa dalam Pencegahan Bullying - Ena Noveria; Muhammad Arif Pribadi; Akmal Muhammad Ali Nasution; Zaskya Adya Mecca; David Rivan; Olvi Sagita; Muzakki Fankas (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
As an integral part of the community service contributions of Universitas Negeri Padang, students play a crucial role in applying various fields of knowledge gained during their studies for the advancement of society across different sectors. In line with this principle, Community Service Program (CSP) students from Universitas Negeri Padang actively participated through the implementation of a socialization program conducted in the Sungai Limau region during the January june 2026 period. The program carries the theme "Bullying Prevention in the School Environment," driven by the high urgency of protecting children against physical, verbal, and cyberbullying. The implementation method followed three systematic stages planning, preparation, and execution utilizing lectures, interactive discussions, and ice breaking techniques to enhance student enthusiasm. The service subjects included students at SDN 18, SDN 26, SDN 12, SDN 22, SDN 41, and SDN 38 Sungai Limau. Observational results indicate that this socialization significantly improved students' understanding of the negative impacts of bullying and the importance of empathy. Despite variations in participation levels at several schools due to logistical constraints, the program overall successfully encouraged students' courage to reject and report bullying incidents. The creation of a safe, inclusive, and conducive school environment for learning highly depends on the sustained synergy between students, teachers, parents, and the broader community.